2013
DOI: 10.1152/jn.00381.2013
|View full text |Cite
|
Sign up to set email alerts
|

Variability and information content in auditory cortex spike trains during an interval-discrimination task

Abstract: Abolafia JM, Martinez-Garcia M, Deco G, Sanchez-Vives MV. Variability and information content in auditory cortex spike trains during an interval-discrimination task. J Neurophysiol 110: 2163-2174, 2013. First published August 14, 2013 doi:10.1152/jn.00381.2013.-Processing of temporal information is key in auditory processing. In this study, we recorded single-unit activity from rat auditory cortex while they performed an interval-discrimination task. The animals had to decide whether two auditory stimuli were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The functional role of the observed neural and behavioral variability in repetitions of the same task is a fundamental question in systems neuroscience [1][2][3][4][5][6][7][8][9][10][11][12][13] and is currently under extensive discussion. The focus has been mainly on the analysis of trial-to-trial variability dynamics in motor [2,[14][15][16][17] or in sensory [4,8,16,[18][19][20] cortical areas; and more recently in frontal regions during decision-making tasks [2,3,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional role of the observed neural and behavioral variability in repetitions of the same task is a fundamental question in systems neuroscience [1][2][3][4][5][6][7][8][9][10][11][12][13] and is currently under extensive discussion. The focus has been mainly on the analysis of trial-to-trial variability dynamics in motor [2,[14][15][16][17] or in sensory [4,8,16,[18][19][20] cortical areas; and more recently in frontal regions during decision-making tasks [2,3,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we investigate this scenario further by focusing on the relationship between optimal choice behavior and shared trial-to-trial variability in rodent OFC [20,41]. The OFC provides a particularly interesting case study, since it has been associated with multiple behaviorally relevant variables in the decision-making task space (e.g., [42][43][44][45][46][47][48][49][50][51]) such as outcomes expectations that guide action [41,52], their desirability [53] or the availability of multiple-valued choices in economic decision making [45] (but see also [54]).…”
Section: Introductionmentioning
confidence: 99%
“…Davies et al ( 2006 ) showed that in motor cortex spike time irregularity increases during the most demanding epoch of a precision grip task. Spike count variability, on the other hand, systematically decreases during a behavioral task being lowest during movement execution (Churchland et al, 2006 , 2010 ; Rickert et al, 2009 ), perceptual processing (Mitchell et al, 2009 ; Churchland et al, 2010 ; Abolafia et al, 2013 ; Ponce-Alvarez et al, 2013 ; Mazzucato et al, 2015 ), attention (Mitchell et al, 2007 ; but see McAdams and Maunsell, 1999 ), or in relation to decision processes (Churchland et al, 2011 ). In addition, Rickert et al ( 2009 ) showed that during movement preparation and execution the FF in motor cortex depends on the amount of prior information about the requested movement.…”
Section: Introductionmentioning
confidence: 99%
“…Davies et al (2006) showed that in motor cortex spike time irregularity increases during the most demanding epoch of a precision grip task. Spike count variability, on the other hand, systematically decreases during a behavioral task being lowest during movement execution (Churchland MM et al 2006, 2010Rickert et al 2009), perceptual processing (Mitchell et al 2009;Churchland MM et al 2010;Abolafia et al 2013;Ponce-Alvarez et al 2013;Mazzucato et al 2015), attention (Mitchell et al 2007; but see McAdams and Maunsell 1999), or in relation to decision processes (Churchland AK et al 2011). In addition, Rickert et al (2009) showed that during movement preparation and execution the FF in motor cortex depends on the amount of prior information about the requested movement.…”
Section: Introductionmentioning
confidence: 99%